COVID-19 vaccine hesitancy scale and its association with actual COVID-19 vaccine uptake in Israel. Issue 9 (24th February 2023) - Grossman-Giron, Ariella; Tzur Bitan, Dana; Shemesh, Sharon; Mayer, Yael; Shiffman, Noga; Bloch, Yuval
Highlights: The COVID-19 vaccine hesitancy scale (C19-VHS) has sound psychometric properties and is predictive of actual uptake of COVID-19 vaccination. Higher hesitancy was observed among younger aged participants and female gender. Older age, female gender, and getting the flu vaccine in the past year were predictive of COVID-19 vaccine uptake. Abstract: Background: The public's willingness to get vaccinated continues to be a source of concern. In this study we assessed the psychometric properties of the COVID-19 vaccine hesitancy scale (C19-VHS) as well as the association between the scale and self-reported past COVID-19 vaccination, approximately two weeks after the national vaccine distribution plan was launched in Israel. Methods: Participants were recruited via an online survey distributed through social media platforms and mailing lists. A total of 650 individuals completed the C19-VHS, the general vaccine hesitancy scale, and the fear of COVID-19 scale, and reported on demographic and pandemic-related characteristics. Principal component and Cronbach's alpha analyses were performed to assess the factor structure and reliability of the scale. Logistic regressions were employed to assess the scale's convergent and discriminative validity. Results: Two factors pertaining to "lack of confidence" (Factor 1) and "risk perception" (Factor 2) emerged. Cronbach's alpha indicated good reliability of Factor 1 (0.93), with lower reliability of Factor 2 (0.72). Younger age was associated with higher risk perception, with women showing less confidence and perceiving greater risks. Lower hesitancy significantly predicted actual COVID-19 vaccine uptake after adjusting for demographic and pandemic-related factors (OR = 1.16, 95%CI 1.11–1.21, p <.001). Older age, being a woman, and receiving the flu vaccine in the past year were also predictive of COVID-19 vaccine uptake. Discussion: The C19-VHS measure shows robust psychometric properties and is associated with actual vaccine uptake. Future studies assessing COVID-19 vaccination attitudes may utilize this scale to assess current COVID-19 vaccine hesitancy in different contexts and cultures.